2015
DOI: 10.5935/0103-5053.20150105
|View full text |Cite
|
Sign up to set email alerts
|

MCM-41 for Meloxicam Dissolution Improvement:in vitroRelease andin vivoBioavailability Studies

Abstract: In this study, MCM-41 was prepared as a carrier for poorly water soluble drugs. Meloxicam (MLX) was selected as model compound. Textural and chemical characterizations were carried out by thermal gravimetric analysis (TGA), scanning electron microscope (SEM), nitrogen adsorption/desorption, X-ray diffraction (XRD) and Fourier transform infrared (FTIR). The in vitro release of MLX was performed at pH 1.2 and 6.8. After loading MLX into MCM-41, its oral bioavailability was compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…The SEM images of MSNs before drug loading (bare MSN) are presented as Supplementary Materials (Figure S1) and reveal agglomerates of rugous spherical and spheroidal particles with broad particle size distribution in the submicrometric range. These morphologies are in good agreement with studies performed by Hassan et al (2015) and Shariatinia and Zahraee (2017), which also reported similar MCM-41 morphologies [ 28 , 29 ]. Regarding its particle size, the submicrometric range is far below the opening of the needle later used for 3D printing of hydrogel HG-MSN-CP; therefore, no blocking is expected during the extrusion process.…”
Section: Resultssupporting
confidence: 92%
“…The SEM images of MSNs before drug loading (bare MSN) are presented as Supplementary Materials (Figure S1) and reveal agglomerates of rugous spherical and spheroidal particles with broad particle size distribution in the submicrometric range. These morphologies are in good agreement with studies performed by Hassan et al (2015) and Shariatinia and Zahraee (2017), which also reported similar MCM-41 morphologies [ 28 , 29 ]. Regarding its particle size, the submicrometric range is far below the opening of the needle later used for 3D printing of hydrogel HG-MSN-CP; therefore, no blocking is expected during the extrusion process.…”
Section: Resultssupporting
confidence: 92%
“…The research literature [28,34,35] confirms that the characteristic absorption peaks of Al-MCM-41 zeolites are located at 1089, 790 and 460 cm −1 , where the broad band at 1089 cm −1 and the band at 790 cm −1 correspond to the asymmetric and symmetric Si-O or Al-O stretching vibrations, and the band at 460 cm −1 indicates the bending vibrations of surface Si-O groups. In addition, all the samples exhibit an HSO 4 − stretching vibration absorption peak at 543 cm −1 [36,37] and a weak characteristic absorption peak for S=O at 1382 cm −1 in addition to the Al-MCM-41 sample [37,38], suggesting that the sulfate group has been successfully anchored on the walls of Al-MCM-41.…”
Section: Modification With So 4 2− /M X O Ysupporting
confidence: 68%
“…Since the framework of Al-MCM-41 consists majorly of silanol groups, the relatively flat peak of Al-MCM-41 at higher temperature shows that there is probably negligible condensation of those silanol on the surface of the prepared catalyst. [20] 29 Si solid-state NMR 29 Si solid-state NMR of zeolite-Y was done to assess the Si/Al ratio of the zeolite NaÀ Y catalyst. The deconvoluted 29 Si solid- The peaks obtained are in good agreement with the literature.…”
Section: Thermogravimetric (Tga) Analysismentioning
confidence: 99%